IFN-γ plays a unique role in protection against low virulent Trypanosoma cruzi strain. - Adele A Rodrigues; Jasson S S Saosa; Grace K da Silva; Flávia A Martins; Aline A da Silva; Cecílio P da Silva Souza Neto; Catarina V Horta; Dario S Zamboni; João S da Silva; Eloisa A V Ferro; Claudio V da Silva (Public Library of Science (PLoS), 2012)
BACKGROUND: T. cruzi strains have been divided into six discrete typing units (DTUs) according to their genetic background. These groups are designated T. cruzi I to VI. In this context, amastigotes from G strain (T. cruzi I) are highly infective in vitro and show no parasitemia in vivo. Here we aimed to understand why amastigotes from G strain are highly infective in vitro and do not contribute for a patent in vivo infection. METHODOLOGY/PRINCIPAL FINDINGS: Our in vitro studies demonstrated the first evidence that IFN-γ would be associated to the low virulence of G strain in vivo. After intraperitoneal amastigotes inoculation in wild-type and knockout mice for TNF-α, Nod2, Myd88, iNOS, IL-12p40, IL-18, CD4, CD8 and IFN-γ we found that the latter is crucial for controlling infection by G strain amastigotes. CONCLUSIONS/SIGNIFICANCE: Our results showed that amastigotes from G strain are highly infective in vitro but did not contribute for a patent infection in vivo due to its susceptibility to IFN-γ production by host immune cells. These data are useful to understand the mechanisms underlying the contrasting behavior of different T. cruzi groups for in vitro and in vivo infection.